Investigation of effect of nintedanib in experimental uveitis model - Yildirim, Hakan; Balbaba, Mehmet; Erdag, Murat; Dal, Ali; Canleblebici, Mehmet; Ilhan, Nevin; Eroksuz, Yesari (Taylor & Francis Ltd, 2022)
Purpose: This study aims to investigate the protective efficacy of nintedanib in experimental uveitis induced by endotoxins. Materials and methods: In this study, 24 Wistar albino rats were randomly divided into three groups: Group I was the healthy control with no uveitis that did not receive any treatment, Group II (sham) group did not receive treatment, and Group III (nintedanib) received oral nintedanib for 10 days. On the 10th day, endotoxin-induced uveitis (EIU) was induced by lipopolysaccharide (LPS) injection in Groups II and III. The clinical activity score was evaluated in all groups at the 24th hour, when uveitis formation was thought to be the most intense after LPS injection. All rats were then killed via anaesthesia. Tumour necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6) levels were measured in their right eyes using the enzyme-linked immunosorbent assay (ELISA) method. Further, histopathological examinations were performed on their left eyes. Results: For Groups I, II, and III, the IL-6 levels were 30.88 +/- 1.79, 36.77 +/- 1.21, and 30.93 +/- 3.96 mg/pr, respectively, and TNF-alpha levels were 50.20 +/- 3.24, 59.87 +/- 2.98, and 50.23 +/- 4.83 mg/pr, respectively. IL-6, TNF-alpha levels and clinical activity score were higher in the sham group compared to the other groups, and it decreased significantly in the treatment group (p < 0.05). Intense inflammatory cell infiltration of the ciliary body, edema and hyperaemia were evident in the sham group compared to the healthy control group (p < 0.05). These pathological findings were significantly decreased in the treatment group compared to the sham group (p < 0.05). Conclusion: Nintedanib may be preferable as a new agent for treating non-infectious uveitis. However, further studies are needed to evaluate its long-term effects, effects on other antiinflammatory pathways, side-effects, and ideal dose optimization.
Keywords: Nintedanib; Tumour necrosis factor-alpha; Interleukin-6; Uveitis